“It Is Not the Robot Who Learns, It Is Me.” Treating Severe Dysgraphia Using Child–Robot Interaction - Gargot, Thomas; Asselborn, Thibault; Zammouri, Ingrid; Brunelle, Julie; Johal, Wafa; Dillenbourg, Pierre; Archambault, Dominique; Chetouani, Mohamed; Cohen, David; Anzalone, Salvatore M. (Frontiers in Psychiatry, 2021)
Writing disorders are frequent and impairing. However, social robots may help to improve children’s motivation and to proposed enjoyable and tailored activities. Here, we have used the co-writer scenario in which a child is asked to teach a robot how to write via demonstration on a tablet, combined with a series of games we developed to train specifically pressure, tilt, speed and letter liaison controls. This set-up was proposed to a 10-year-old boy with a complex neurodevelopmental disorder combining Phonological Disorder, Attention Deficit/Hyperactivity Disorder, Dyslexia, and Developmental Coordination Disorder with severe dysgraphia. Writing impairments were severe and limited his participation in classroom activities despite two years of specific support in school and professional speech and motor remediation. We implemented the setup during his occupational therapy for 20 consecutive weekly sessions. We found that his motivation was restored; avoidance behaviors disappeared both during sessions and at school; handwriting quality and posture improved dramatically. In conclusion, treating dysgraphia using child robot interaction is feasible and improves writing. Larger clinical studies are required to confirm that children with dysgraphia could benefit from this set up.